2010
DOI: 10.1007/s00403-009-1025-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of psoriasis in Korean adults and children: correlation with serum anti-streptolysin O titers

Abstract: Psoriasis is a relatively common disorder in children and can be triggered by an upper respiratory tract infection. The aim of this study was to compare the clinical features of psoriasis in children and adult. In addition, we evaluated the relationship between anti-streptolysin O (ASO) titers and the clinical features of psoriasis. A total of 30 childhood psoriasis patients and 30 adult psoriasis patients were evaluated. Childhood psoriasis had a facial predominance when compared with the adult psoriasis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
2
15
0
1
Order By: Relevance
“…The numbers found in the Dutch cohort (73·3%; Caucasians 83·8%; others 25%) compared favourably with data from Australia 2 (71%) and Faroe Islands 6 (91%), which have a predominantly Caucasian population. In contrast, data from the SG group (13·6%) are similar to data from Korea 7 (13·3%) and India 5,8 (4·5%, 9·8%). A Chinese survey revealed a positive family history in 34·4% 4 .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The numbers found in the Dutch cohort (73·3%; Caucasians 83·8%; others 25%) compared favourably with data from Australia 2 (71%) and Faroe Islands 6 (91%), which have a predominantly Caucasian population. In contrast, data from the SG group (13·6%) are similar to data from Korea 7 (13·3%) and India 5,8 (4·5%, 9·8%). A Chinese survey revealed a positive family history in 34·4% 4 .…”
Section: Discussionsupporting
confidence: 54%
“…The most outstanding result of this study was the disparity in familial distribution between the two groups. It is known that 4·5–91% of children with psoriasis have a family history of psoriasis 2–8 . The numbers found in the Dutch cohort (73·3%; Caucasians 83·8%; others 25%) compared favourably with data from Australia 2 (71%) and Faroe Islands 6 (91%), which have a predominantly Caucasian population.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Twenty‐five of these 33 studies found that less than 50% of children with psoriasis were boys (range 35·9–49%). The male to female ratio was provided in 16 studies and varied from 1·14 : 1 to 1 : 2·33 . Matusiewicz et al .…”
Section: Resultsmentioning
confidence: 99%
“…Literatürde infeksiyon varlığı ile PASI değerleri arasındaki ilişkiyi araş-tıran çalışmalar yeterli olmasa da, boğaz kültüründe beta hemolitik streptekok üreyen plak psoriyazisli olgularda ve ASO değerleri yüksek olan plak psoriyazisli çocuk olgularda PASI değerlerinin anlamlı olarak daha yüksek olduğu bildirilmiştir. 19,25 Bununla birlikte Yıldırım ve arkadaşları tarafından psoriyazis ve parvovirüs B19 arasındaki ilişkinin araştırıldığı bir diğer çalışmada viral DNA yükü ile psoriyazis klinik tipi ve PASI değerleri arasında anlamlı bir ilişki saptanmamıştır. 26 Bizim çalışmamızda ise GÜİ saptanan aktif ve stabil psoriyazisli olgularda GÜİ olmayanlara göre ortalama PASI değerleri anlamlı olarak daha yüksek saptanmış, ayrıca her iki grupta da PASI değeri ≥10 olan olgularda GÜİ varlığının arttığı görülmüştür.…”
Section: Discussionunclassified